Dose-dependent effect of early antiplatelet therapy in acute ischaemic stroke - Meves, Saskia H.; Overbeck, Ursula; Endres, Heinz G.; Krogias, Christos; Neubauer, Horst (Thrombosis and Haemostasis, 2012)
Antiplatelet agents are essential in treating patients with acute ischaemic stroke (AIS) to prevent recurrent ischaemic events. The aim of this study was to evaluate the effectiveness of early antiplatelet therapy with different aspirin (ASA) dosages in patients with AIS. This observational study included 454 patients with AIS in whom antiplatelet treatment was initiated. The antiplatelet effect was determined by whole blood aggregometry within 48 hours after antplatelet therapy was initiated. An impedance change exceeding 0 Ω after stimulation with arachidonic acid was defined as ASA low response (ALR) and ≥5 Ω in ADP-stimulated specimen as clopidogrel LR. Of the study group 53.5% patients were treated with 200 mg ASA orally, 27.5% with 500 mg ASA intravenously, 8.6% with 100 mg ASA orally, and 7.7% with 75 mg clopidogrel. A dose-dependent antiplatelet effect of ASA treatment was found: 18.4% of patients with 500 mg ASA intravenously were ALR, in contrast to 32.5% on 200 mg and 35.9% on 100 mg ASA orally. Clopidogrel treatment without a loading dose resulted in a high proportion of LR (45.7%). Using the propensity score method revealed a three times higher risk for ALR for patients treated with ASA 200 mg [odds ratio 2.99 (1.55–5.79)] compared to treatment with ASA 500 mg. In conclusion, initiating antiplatelet therapy in patients with AIS resulted in a dose-dependent insufficient platelet inhibitory effect. Our findings suggest using a loading dose of 500 mg ASA intravenously as this seems to be favourable when a sufficient early platelet inhibitory effect is wanted.ClinicalTrials.gov Identifier: NCT01273935
Keywords: Aspirin; acute cerebrovascular ischaemia; platelet function testing; stroke prevention; antiplatelet agents